Economic Analysis of Sustainable Admission Business in Development Area Tanete Riattang East Bone - Toto Hardianto; Yakub Suleman; Mustafa Mustafa; Feby Triadi (Program Pascasarjana Universitas Negeri Makassar, 2022)
The results of this study aim to determine the pattern of business activities and application of pond cultivation technology and the level of feasibility per unit of pond land. Starting from January - July, 2020, in Tanete Riattang Timur District. The pond business patterns are grouped into milkfish monoculture (Chanos chanos fork), milkfish polyculture (Chanos chanos fork) and seaweed (Gracillaria verrucosa), milkfish (Chanos chanos fork) and shrimp (Litopenaeus vannamei) polycultures with narrow (< 2 hectares), medium (2-5 hectares) and broad (> 5 hectares) scales. The results of the study show that almost all of the ponds in the Tanete Riattang Timur sub-district have entisol soil types. The soil texture is fine and coarse, the slope of the pond land is 1-9%. The appropriate distance for aquaculture is 50 – 500 meters from the river bank, water pH ranges from 7.5 – 8, salinity ranges from 15 – 29 ppt, water temperature ranges from 29 – 32 0C. GIS analysis of total pond area ±817.015 Ha. Respondents were 59 Fishery Households (RTP). The financial feasibility of monoculture milkfish (Chanos chanos fork) DF 12%, the highest is the NPV of Rp. 57,267,164. Net B/C ratio 1.77; IRR of 29.03%. The financial feasibility of milkfish (Chanos chanos fork)-shrimp polyculture where the highest DF 12% is the NPV of Rp. 88,857,765, Net B/C ratio of 2,099; IRR of 35.48%. The financial feasibility of polyculture of milkfish (Chanos chanos fork) seaweed (Gracillaria verrucosa) where the DF is 12% with the highest value, namely NPVRp. 90,665,055; Net B/C ratio of 2,099; IRR is 33.67%. The conclusion is that the land suitability category in Tanete Riattang Timur District consists of very suitable.